PROSES KOLABORASI DALAM PENGEMBANGAN DESA WISATA BALONG KECAMATAN JEPON KABUPATEN BLORA - Sriajeng Pramugita Salsabilla; R. Slamet Santoso (Journal of Management and Public Policy, 2026)
Balong Tourism Village in Jepon District, Blora Regency, has significant tourism potential. However, its development remains hampered by ineffective collaboration between the government, community, and private sector. This study analyzes the collaborative process in tourism village development using a collaborative governance approach, emphasizing the importance of active involvement of all stakeholders. The results indicate that despite ongoing collaboration, the community's role remains limited, government support is suboptimal, and private sector involvement is minimal. The collaboration is primarily driven by the Tourism Awareness Group (Pokdarwis), but this lacks adequate structural support. The collaborative process, which should include face to-face dialogue, trust-building, and commitment to shared goals, remains suboptimal, hampering the achievement of sustainable tourism village management. Strengthening local institutional capacity and implementing more inclusive and structured collaboration are key to the successful development of a more participatory and sustainable Balong Tourism Village.